Improving Health Information Systems for Universal Health Coverage in the Philippines - Catherine Agas Chung; Jenilyn Ann Vergara Dabu; Fiona Rose Andres Norada; Arianna Maever Loreche; Veincent Christian F. Pepito; Manuel M. Dayrit (Public Health Challenges)
ABSTRACT Health information systems are a key building block of a well‐functioning health system and are a vital component in the implementation of universal health coverage. The Philippines's current transition toward universal health coverage had attendant health information system reforms, such as the establishment of the country's National Health Data Repository and the Health Sector Enterprise Architecture. However, many issues remain in this transition, such as insufficient investments in health information systems, poor reliability of health information systems, technical support delays, data quality issues, and cybersecurity issues. We recommend making health data portable throughout the health system while adhering to data privacy laws, investing in internet connectivity, information technology, and capacity building for human resources, and improving implementation of current policies and guidelines to fully harness the potential of health information systems in making universal health coverage a reality in the Philippines.